(untitled) (Indian Journal of Arid Horticulture, 2025)
Pea occupies an important position amongst the vegetable crops of India and is one of the few crops that can be successfully grown during the winter season in In- dia. However, Ascochyta blight caused by Ascochyta pisi Lib. is responsible for substantial yield losses in pea to the tune of 30-75 per cent under favourable conditions for dis- ease development (Roger and Tivoli, 1996). The disease is polycyclic and can develop rapidly during periods of wet weather and moderate temperatures.